2014
DOI: 10.1155/2014/262710
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Culture Conditions (Sucrose, pH, and Photoperiod) forIn VitroRegeneration and Early Detection of Somaclonal Variation in Ginger Lime (Citrus assamensis)

Abstract: Various explants (stem, leaf, and root) of Citrus assamensis were cultured on MS media supplemented with various combinations and concentrations (0.5–2.0 mgL−1) of NAA and BAP. Optimum shoot and root regeneration were obtained from stem cultures supplemented with 1.5 mgL−1 NAA and 2.0 mgL−1 BAP, respectively. Explant type affects the success of tissue culture of this species, whereby stem explants were observed to be the most responsive. Addition of 30 gL−1 sucrose and pH of 5.8 was most optimum for in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…Most of the reports are mainly focussed on Plant Growth regulators (PGRs), but, studies on the role of other factors such as gelling agents, light intensity, medium pH, silver nitrate etc. in shoot organogenesis remains very limited (Cui et al 2000, Kumar et al 2003, Kumar et al 2010, Yaacob et al 2014. Medium pH and gelling agents are seen as one of the most important factors due to their role in regulation of medium nutrient solubility and their uptake by the explants (George 1993, Bhatia andAshwath 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reports are mainly focussed on Plant Growth regulators (PGRs), but, studies on the role of other factors such as gelling agents, light intensity, medium pH, silver nitrate etc. in shoot organogenesis remains very limited (Cui et al 2000, Kumar et al 2003, Kumar et al 2010, Yaacob et al 2014. Medium pH and gelling agents are seen as one of the most important factors due to their role in regulation of medium nutrient solubility and their uptake by the explants (George 1993, Bhatia andAshwath 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, Shi et al [44] has reported that the medium pH between 5.5 and 7.5 is suitable for apple tissue culture. Yaacob et al [45] stated that shoot formation occurred faster (30 days) and shooting percentage also higher at pH 5.8, compared to pH 4.8 and 6.8 in Citrus assamensis. Thus, seeds of V. phyrigium tolerate a range of pH in tissue culture conditions (5.5-7.0).…”
Section: Resultsmentioning
confidence: 99%
“…Contrariwise, as per the search for the literature in 'Google Search', there is no finding on direct regeneration of shoots from cotyledon of citrus species. Ample references are also available on direct shoot multiplication from nodal segments [1,6,7,9,15,16], shoot tips [6,7,16,17], cotyledonary node [18,19], axillary buds [20] and meristem culture [21] Direct plantlet regeneration from leaf segments represent a promising tool for massmultiplication of citrus keeping the genetic fidelity intact. To date, direct organogenesis from leaf explants of C. jambhiri is not available.…”
Section: Discussionmentioning
confidence: 99%